The effects of English language proficiency on performance and competence of learners in the rural secondary schools at Koloti Circuit - Makgoka, Malesetja Patricia (My University, 2011)
This study investigated the effects of English Language Proficiency on Performance and Competence of Learners in the Rural Secondary Schools at Koloti circuit. The primary aim of this study was to establish whether English Language Proficiency had an effect on learners’ competence and performance in English as a Second Language and to establish the root cause of the problem of poor language proficiency. The background to this study was outlined, which was followed by an intensive literature review on the topic. The study followed a case study design which utilized 39 learners from the sampled schools in Koloti Circuit. Data was collected from diagnostic tests which were written by learners, questionnaires which were distributed to learners and parents, and interviews which were conducted with teachers and learners. The study showed that learners have serious deficiencies in reading, listening, speaking and writing skills which affect their competence and performance. The study also showed that this deficiency is attributed to teachers who need intensive in-service training in these skills. This study was based on Krashen’s and Cummin’s theories of second language learning.
Thesis (M.ED.) -- University of Limpopo, 2011
Keywords: Language proficiency; Learners competence; Language learning; 372.6521; Secondary Level English Proficiency Test